Learning and intelligent optimization : 10th International Conference, LION 10, Ischia, Italy, May 29-June 1, 2016, revised selected papers /: 10th International Conference, LION 10, Ischia, Italy, May 29-June 1, 2016, revised selected papers. (2016) - Unknown
No abstract available